(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Lifestyle is the way of living, reflects an individual’s attitudes, value, or world view. It is assumed to be an important factor affecting health. Objectives: To identify pattern of and determinants of life styles among male and female medical students, Jeddah, KSA. Methods: A cross-sectional survey included 204 male and female medical students at private medical college. A specially designed pre-coded closed ended pilot tested online questionnaire in English and Arabic was used. It included socio-demographic characteristics and lifestyle habits (sleeping pattern, activity level, feeding pattern, smoking, medication and medical history). Chi-square, independent t-test and bivariate analysis were conducted. Statistical significance was at p less than 0.05. Results: There were significant differences regarding: activity level (p=0.001), smoking (p=0.001), self-medication (p=0.000), exposure to stressful life events (p=0.021) and total life style score (p=0.001). Gender was negatively correlated with activity level score (r=-.236, p=0.001), smoking score (r=.221, p=0.001), self-medication score (r=-.337, p=0.000) and stressful life events score (r=-.158, p=0.24). The feeding pattern score was affected by age (r=0.184, p=0.008), socio-economic level (r=0.188, p= 0.007), educational level (r=0.191, p=0.006) BMI (r=0.191, p=0.006) and chronic medical condition (r=0.144, p=0.040). Both smoking and self-medication scores were affected by chronic medical conditions (r=0.206, p=0.003 and r=0.247, p=0.000 respectively) Conclusion: The total healthy life style score was significantly low. Gender has an effect on activity level, smoking, self-medication and stressful life events scores. Feeding pattern score is affected by age, socio-economic level, education level, body mass index and chronic medical condition.